A Repeated Halving Approach to Fabricate Ultrathin Single‐Walled Carbon Nanotube Films for Transparent Supercapacitors. Issue 4 (1st November 2012) - Niu, Zhiqiang; Zhou, Weiya; Chen, Jun; Feng, Guoxing; Li, Hong; Hu, Yongsheng; Ma, Wenjun; Dong, Haibo; Li, Jinzhu; Xie, Sishen
Abstract : Ultrathin SWCNT transparent and conductive films on flexible and transparent substrates are prepared via repeatedly halving the directly grown SWCNT films and flexible and transparent supercapacitors with excellent performance were fabricated.